Synthesis of soluble, alkyne-substituted trideca- and hexadeca-starphenes - Rüdiger, Elias; Porz, Michael; Schaffroth, Manuel; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2014)
Abstract Two literature-known TIPS-ethynyl-dibromoacenes were prepared and employed to synthesize cyclotrimers by using Yamamoto coupling conditions. Two large, well-soluble starphenes were isolated in good yields. Crystallographic characterization verifies the triangular shape and shows significant differences in crystal packing.
Gesehen am 07.08.2020